Market Discipline, Deposit Insurance, and Competitive Advantages: Evidence from the Financial Crisis - Florian Kaposty; Andreas Pfingsten; Christian Domikowsky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
First, this study empirically explores whether it is possible to offer full insurance for non-financial depositors whilst maintaining market discipline. Second, we analyze whether a more credible deposit insurance scheme can be a competitive advantage for banks in a systemic crisis. We find (1) evidence for market discipline, and (2) banks ceteris paribus achieving higher growth rates of customer deposits in the financial crisis if they are part of a credible deposit insurance scheme.
Keywords: G01; G21; G28; 330